The Effects of Positive Self-Talk Among Winning Athletes in Martial Arts: A Mixed-Methods Study - Mortejo, Alonzo L; Mortejo, Jesselyn C (Universitas Negeri Padang, 2024)
Background and aim. Martial arts require the integration of physical abilities and psychological readiness, particularly in challenging competitive situations. One psychological strategy widely used by athletes is positive self-talk, which plays a role in maintaining focus, self-confidence, and emotional regulation during competition. Although the benefits of self-talk have been widely discussed, research that specifically explores its role among winning martial arts athletes remains limited. Therefore, this study aims to examine the effects of positive self-talk on psychological aspects that support the performance of winning martial arts athletes.Methods. This study employed a mixed-methods design. The research population consisted of collegiate-level arnis, karate, and taekwondo athletes who were actively competing at several public colleges and universities in the Philippines. The quantitative sample included 50 athletes selected using purposive sampling. Quantitative data were collected using a 15-item Likert-scale questionnaire with five response points that had been tested for feasibility and reliability. The qualitative phase involved seven national- or international-level winning athletes through semi-structured interviews. Quantitative analysis was conducted using a one-sample t-test with a test value of 3, while qualitative data were analyzed thematically.Results. The quantitative results showed that all psychological variables had mean scores that were significantly higher than the midpoint of the Likert scale (p < 0.001). Focus during competition obtained the highest score (M = 4.52, SD = 0.41), followed by self-confidence (M = 4.47, SD = 0.36), performance under pressure (M = 4.38, SD = 0.48), and anxiety reduction (M = 4.20, SD = 0.55). The qualitative findings revealed that positive self-talk helped athletes maintain mental clarity, strengthen self-belief, manage emotions, and sustain performance in high-pressure situations.Conclusions. This study demonstrates that positive self-talk functions as an important psychological regulation mechanism for winning martial arts athletes. These findings imply that coaches and sport practitioners should systematically integrate positive self-talk training into mental preparation programs to support athletes’ performance consistency in competition.